Surgical treatment of glaucoma with filtration bleb activation of a patient with Sturge — Weber syndrome: a clinical case - T. N. Savranova; V. U. Rozukulov; A. F. Yusupov; D. A. Asadov; S. S. Saidzhonov (Российский офтальмологический журнал)
Purpose: to describe surgical treatment of glaucoma of a patient with Sturge — Weber — Krabbe syndrome. We present a clinical case of a patient with Sturge — Weber — Krabbe syndrome who sought assistance with us due to secondary stage III glaucoma with moderately elevated intraocular pressure. The examination revealed a cutaneous hemangioma of the frontal, and zygomatic area of the left half of the face, the upper and the lower eyelids, and conjunctival and episcleral hemangioma of the left eye. Since local hypotensive drug therapy produced no effect, the patient was offered a surgical treatment: sinus trabeculectomy. A pronounced hemorrhage from the conjunctival vessels, the episclera and choroidal vessels that occurred during the operation increased its duration, but severe complications could be avoided. A hyphema that appeared during the operation was almost completely washed out and dissolved within 5 days. Since scarring processes of the filtration zone were activated in the postoperative period, we resorted to an active tactics of the patient’s management, namely the needling of the filtration zone with the use of antimetabolites and corticosteroids.Conclusion. Sinus trabeculectomy is an effective method of IOP normalization in glaucoma patients with Sturge — Weber — Krabbe syndrome. Active management of the patient in the postoperative period of the case described allowed us to avoid severe intra- and postoperative complications and to achieve stable clinical and functional results.